Arabidopsis thaliana plants lacking the ARP2/3 complex show defects in cell wall assembly and auxin distribution - Pratap Sahi, Vaidurya; Cifrová, Petra; García-González, Judith; Kotannal Baby, Innu; Mouillé, Gregory; Gineau, Emilie; Müller, Karel; Baluška, František; Soukup, Aleš; Petrášek, Jan; Schwarzerová, Katerina (Annals of botany, 2018)
BACKGROUND AND AIM: The cytoskeleton plays an important role in the synthesis of plant cell walls. Both microtubules and actin cytoskeleton are known to be involved in the morphogenesis of plant cells through their role in cell wall building. The role of ARP2/3-nucleated actin cytoskeleton in the morphogenesis of cotyledon pavement cells has been described before. Seedlings of Arabidopsis mutants lacking a functional ARP2/3 complex display specific cell wall-associated defects. METHODS: In three independent Arabidopsis mutant lines lacking subunits of the ARP2/3 complex, phenotypes associated with the loss of the complex were analysed throughout plant development. Organ size and anatomy, cell wall composition, and auxin distribution were investigated. KEY RESULTS: ARP2/3-related phenotype is associated with changes in cell wall composition, and the phenotype is manifested especially in mature tissues. Cell walls of mature plants contain less cellulose and a higher amount of homogalacturonan, and display changes in cell wall lignification. Vascular bundles of mutant inflorescence stems show a changed pattern of AUX1-YFP expression. Plants lacking a functional ARP2/3 complex have decreased basipetal auxin transport. CONCLUSIONS: The results suggest that the ARP2/3 complex has a morphogenetic function related to cell wall synthesis and auxin transport.
Keywords: proteiny huseníčku; regulátory růstu rostlin; Arabidopsis Proteins; kyseliny indoloctové; buněčná stěna; Cell Wall; Actin-Related Protein 2-3 Complex; Indoleacetic Acids; Plant Growth Regulators; Arabidopsis; komplex proteinů 2-3 souvisejících s aktinem